2020
DOI: 10.3390/ijerph17145036
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Careers of University Students in Educational Practices as Factors of Individual Differences in Learning Environment and Psychological Factors during COVID-19

Abstract: The present research was carried out in Spain during the COVID-19 pandemic following emergency school closures in an attempt to avoid the spread of infection. As a result, university students undertaking the final year of education degrees (teaching placements) have been obliged to deliver their teaching from home, adapting their teaching contexts to learning in virtual settings. A novel instrument was designed and validated in order to analyze the impact of learning environments and psychological factors in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 76 publications
2
14
0
2
Order By: Relevance
“…As a result of the increase in the time spend on social media, the students have become more exposed to read, heard, or see news related to the COVID-19 and therefore they were psychologically affected. Similar findings were previously mentioned in the studies conducting during the COVID-19 pandemic [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. It was reported that the students were experiencing psychological issues related to panic, depression, stress, anger, anxiety, sadness, fear confusion, as well as social dysfunction during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…As a result of the increase in the time spend on social media, the students have become more exposed to read, heard, or see news related to the COVID-19 and therefore they were psychologically affected. Similar findings were previously mentioned in the studies conducting during the COVID-19 pandemic [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. It was reported that the students were experiencing psychological issues related to panic, depression, stress, anger, anxiety, sadness, fear confusion, as well as social dysfunction during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, a value above 0.14 is considered high. This was observed when analysing the results of eta-squared test in relation to satisfaction, which denotes that they are satisfied with the quality management within their higher education institution, and with the groups that also consider that quality is adequate [72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…It is explained by the fact that, except for daily routine women have at home, they now have to prepare and record online lectures-sometimes only having the option to do it at night when their children are asleep. In a survey of 441 university students exploring the COVID-19 impact on learning, Olmos-Gómez has found out that (among others) 75.25% of the respondents were able to solve a problem that arises with the help of tools like email or Facebook and 78.75% consider that their ties with family and friends have become stronger during self-isolation [9]. Studying the impact of social media in universities worldwide, Obaid AI-Youbi et al have analyzed the Twitter account of a university in Saudi Arabia and revealed that, in the pandemic period, this account was successfully used as a powerful tool for communicating critical policy-making as well as issues related to teaching and learning [10].…”
Section: Global Education Policiesmentioning
confidence: 99%